Actresses as working women : their social identity in Victorian culture - Davis, Tracy C., 1960- (Gender and performance., 1991)
Using historical evidence and personal accounts, Davis examines the reality of conditions for òrdinary' actresses, their working environments, employment patterns, and the reasons why acting continued as a popular though insecure profession.